Analysis of pathogenic variants from the ClinVar database in healthy people using next-generation sequencing. (30th August 2017) - RANČELIS, TAUTVYDAS; ARASIMAVIČIUS, JUSTAS; AMBROZAITYTĖ, LAIMA; KAVALIAUSKIENĖ, INGRIDA; DOMARKIENĖ, INGRIDA; KARČIAUSKAITĖ, DOVILĖ; KUČINSKIENĖ, ZITA AUŠRELĖ; KUČINSKAS, VAIDUTIS
Summary: Next-generation sequencing (NGS) became an effective approach for finding novel causative genomic variants of genetic disorders and is increasingly used for diagnostic purposes. Public variant databases that gather data of pathogenic variants are being relied upon as a source for clinical diagnosis. However, research of pathogenic variants using public databases data could be carried out not only in patients, but also in healthy people. This could provide insights into the most common recessive disorders in populations. The study aim was to use NGS and data from the ClinVar database for the identification of pathogenic variants in the exomes of healthy individuals from the Lithuanian population. To achieve this, 96 exomes were sequenced. An average of 42 139 single-nucleotide variants (SNVs) and 2306 short INDELs were found in each individual exome. Pooled data of study exomes provided a total of 243 192 unique SNVs and 31 623 unique short INDELs. Three hundred and twenty-one unique SNVs were classified as pathogenic. Comparison of the European data from the 1000 Genomes Project with our data revealed five pathogenic genomic variants that are inherited in an autosomal recessive pattern and that statistically significantly differ from the European population data.